A representative workforce: the BME police recruitment target and the politics of enumeration and categorisation. Issue 9 (19th August 2014) - Murji, Karim; Williams, Colin
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose To examine the inter-relationship between target setting, racial categories and racism via the case of a race employment target set for the police. Drawing on and extending public administration and governmentality perspectives, the work explores the shifting politics of enumeration and categorisation within a set of organisational manoeuvres. Design/methodology/approach The data is qualitative and mainly based on interviews with senior figures involved in managing the organisational response to the target, as well as some documentary sources. Findings The discussion reveals that both racial enumeration and categorisation are contested rather than fixed, but that debates about it ebb and flow in variable and uneven ways. They are the subject of manoeuvring around the number itself and of what counts as race. This indicates the complexity of governing race targets, which appear set but are made fluid in various ways. Research limitations/implications The research is based on interviews with senior and prominent figures involved in governance who spoke 'off the record', as described in the article. These conversations are not in the public domain and the justification for using them is that they reveal the thinking behind the public debate about the BME target, as well as a process of negotiation and manoeuvring. Originality/value The BME target has been the subject of considerable media and political attention, plus some academic research. The article presents a new and unique account of the target as it was implemented. It is of value to researchers interested in racism and policing interested in the organisational background that shaped the public debates about the target.